1980
DOI: 10.1111/j.1365-2265.1980.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo‐pituitary Ovarian Function in Thirty‐one Women With Chronic Alcoholism

Abstract: SUMMARY A study of hypothalamo‐pituitary function was carried out in chronic alcoholic women aged 29–66 years, with chronic pancreatitis or cirrhosis of the liver. Amenorrhoea was present in most of them (67%). The hormonal investigation included assessment of basal plasma steroids, gonadotrophin and prolactin values, followed by an anterior pituitary function test. Clomiphene stimulation and/or hCG tests were performed. The subjects were divided into four groups according to their oestrogen status on the one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 22 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…We are unaware of any previous studies involving LHRH stimulation of LH after chronic ALC exposure in immature or mature monkeys of both sexes, or in ALC-dependent women. However, LHRH-induced LH release was shown to be unaffected in alcoholic men (37), and in alcoholic women during abstinence when compared with nonalcoholic controls (24,38). Further evidence for an unimpaired LH response to LHRH comes from studies using adult female rats (39,40), adult female rhesus monkeys (41), and men (42) after acute ALC exposure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We are unaware of any previous studies involving LHRH stimulation of LH after chronic ALC exposure in immature or mature monkeys of both sexes, or in ALC-dependent women. However, LHRH-induced LH release was shown to be unaffected in alcoholic men (37), and in alcoholic women during abstinence when compared with nonalcoholic controls (24,38). Further evidence for an unimpaired LH response to LHRH comes from studies using adult female rats (39,40), adult female rhesus monkeys (41), and men (42) after acute ALC exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Chronic ALC exposure also caused suppressed levels of LH in mid-pubertal boys (7), adult female rhesus monkeys (23), alcoholic women (24,25), and in immature and mature rats of both sexes (26,27). This study is the first to assess hypothalamic and pituitary function in immature female monkeys that were exposed chronically to ALC.…”
Section: Discussionmentioning
confidence: 95%
“…Women who report episodic heavy social drinking also report menstrual cycle disorders including dysmenorrhea, premenstrual discomfort and 'heavy menstrual flow (Wilsnack et al 1984). Chronic alcoholism is associated with even more severe disruptions of menstrual cycle function including persistent amenorrhea, anovulation, luteal phase dysfunction and ovarian pathology (Moskovic 1975;Ryback 1977;Hugues et al 1980;Valimaki et al 1984).…”
Section: Discussionmentioning
confidence: 97%
“…Cigarette smoking also increases the risk for coronary heart disease and that risk is accentuated by oral contraceptive use (Glynn and Cullen 1985). Moreover, both tobacco smoking and alcohol abuse may have deleterious effects on female reproductive function (Gritz 1980; A Report of the Surgeon General 1980; Hugues et al 1980;Van Thiel and Gavaler 1982;Mello 1987).…”
mentioning
confidence: 99%
“…Sexual dysfunction with infertility, loss of libido, irregular menses and amenorrhoea may accompany chronic alcohol abuse, especially in those with liver diseases (1)(2)(3)(4). It has been shown that menopause often occurs at an earlier age in female alcoholics (5,6) both in cirrhotics and non-cirrhotics.…”
mentioning
confidence: 99%